Determinan Inflasi dan Pengangguran di Negara Asean - Listiana, Yufita; Sariyani, Sariyani (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
Unemployment and inflation are macro problems that are often faced by a country. This problem can trigger social and political problems. This study aims to analyze the influence between inflation and unemployment in ASEAN countries. The data used are inflation and unemployment data taken from the World Bank website. This research method uses panel data regression, which is a regression model that combines 1991-1209 Time Series data and Cross Sections from 10 ASEAN countries. The results showed that unemployment has a significant effect on inflation in ASEAN countries, the government is expected to maintain inflation and unemployment stability.